Tantangan Dalam Implementasi Model Integrasi Industri Perkapalan Di Indonesia - Firmansyah, Mohammad Rizal; Djafar, Wihdat (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
Indonesian shipbuilding Industry plays significant roles in supporting the economics of the country in the utilization of sea resources, the distribution of natural resources as well as interconnecting people between islands. Hence, it is significant for this industry to survive and keep growing and being competitive not only to fulfill the domestic need on ships but also for export to overseas. Support from the Indonesian government with the policy to build all ships which are operated domestically in the Indonesian shipyards is needed. In the global level, the individual shipyard is relatively difficult to compete with the overseas shipyard. This is because the current global competition is not between individual shipyards but between collaboration shipyards. One of the reasons is there is no collaboration model between shipyards which appropriate with the condition of Indonesian shipyards herself can be found in the literature. This paper discusses an integration model for 4 Indonesian BUMN shipyards which is based on the domestic shipyards characteristics and challenges faced in the implementation stages.